«САЯТХАН-ҲАМРА» ДӘСТАНЫНДАҒЫ КУЛЬМИНАЦИЯЛЫҚ ШЕШИМЛЕР - Максетова, Ф.А. (FAN va JAMIYAT, 2019)
In the article, in the result of studying the dastan «Sayathan-Hamra», we have an opportunity to evaluate the national characteristics of the products of national creativity, customs and traditions. The article reveals that its plots, episodes, motifs in the content of creation, having complete characters. Karakalpak jirau, using their programmatic motive in choosing the plot, worked on this issue. The author of the article analyzes that the factors contributing to the development of event have a single compositional direction, and also the Karakalpak version has its own peculiarities.